2015
DOI: 10.1093/aobpla/plv064
|View full text |Cite
|
Sign up to set email alerts
|

Leaf economics of evergreen and deciduous tree species along an elevational gradient in a subtropical mountain

Abstract: We used leaf economics spectrum (LES) theory to explain the bimodal elevational distribution of evergreen tree species, which is one of the most puzzling biogeographic patterns in the world. Our results suggest that elevation acts as an environmental filter to both select the locally adapted evergreen and deciduous species with sufficient phylogenetic variation and distinct leaf economic strategies and regulate their distribution along the elevational gradient based on their coordinated spreading of phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 69 publications
3
24
0
Order By: Relevance
“…3) in agreement with Reich et al (1999). Under European temperate climate condition, deciduous species are generally characterized by high SLA and hence a faster return of energy investment and transpiration during summer growing season (Bai et al 2015). A recent study by Bochet and García-Fayos (2015) showed that SLA was a relevant trait for indicating plant competitivity and the establishment success on road embankments in semi-arid environment.…”
Section: Discussionsupporting
confidence: 66%
“…3) in agreement with Reich et al (1999). Under European temperate climate condition, deciduous species are generally characterized by high SLA and hence a faster return of energy investment and transpiration during summer growing season (Bai et al 2015). A recent study by Bochet and García-Fayos (2015) showed that SLA was a relevant trait for indicating plant competitivity and the establishment success on road embankments in semi-arid environment.…”
Section: Discussionsupporting
confidence: 66%
“…Physiological and phenological characteristics, such as leaf water potential and leaf habit, have also been used for the same purpose, but to a lesser extent ( e.g ., Bai et al . ). The lack of interrelation between tree deciduousness and the characteristics examined in this study strengthens the idea that in wet forests, isohydry and anisohydry, as well as evergreeness and deciduousness, do not correlate in the same way as they do in dry forests.…”
Section: Discussionmentioning
confidence: 97%
“…Even after accounting for phylogeny, broad‐leaved deciduous tree species have a more acquisitive leaf strategy than evergreens and have higher leaf water, N and P content (Bai et al. ). Evergreen trees often have inferior photosynthetic capacity (Baldocchi et al.…”
Section: Introductionmentioning
confidence: 99%